PENGARUH PENGGUNAAN TEPUNG DAUN Indigofera zollingeriana DALAM RANSUM TERHADAP KUALITAS INTERNAL TELUR AYAM RAS - Mariana, Irma; Sutrisna, Rudy; Riyanti, Riyanti (Jurnal Riset dan Inovasi Peternakan, 2017)
The research aims to know the effect of using leaf meal of Indigofera zollingeriana in rations on internal egg quality and know optimal treatment on the internal egg quality. This research was conducted on April-June 2017 covering step of Indigofera zollingeriana meal production in Manunggal Farmer Group, Purwodadi Village, Adiluwih Sub-district, Pringsewu District and step of feeding trial treatment ration in laying hens farm CV. Varia Agung Jaya Farm, Varia Agung Village, Seputih Mataram Sub District, Central Lampung District. Fourty eight laying hens at 32 weeks of age used. This research use Completely Randomized Design (CRD) with 4 treatments and 6 replication leaf meal Indigofera zollingeriana R0: 0%; R1: 5%; R2: 10%; R3: 15%. Obtained  data were analyzed with the assumptions of variance by 5% or 1%, the results were significantly different in the advanced test using orthogonal polynomials, and showed that the albumen index and yolk index value was not significantly different (P> 0,05), and the yolk color score was very significant (P <0,01) with regression equation ŷ = 7,33 + 1,83x.  Obtained the highest point that is on use of leaf meal Indigofera zollingeriana in a rations of 15% increase of yolk color. Keywords:  Indigofera zollingeriana leaf, Rations, Eggs and Internal Egg Quality